Psicodrama pedagógico: pesquisa-intervenção com crianças com queixa escolar - Gondim, Silvana Monteiro (2016)
The object of this research-intervention was the Pedagogical Psychodrama with children with school problems. Its general objective is analyze the contribution of Pedagogical Psychodrama at psychopedagogic attendance with school problems. As the especific objective is the search of identify what are the school complaints about the children; see how children express themselves on different techniques of teaching psychodrama; verify if the ways which children express themselves in pedagogical psychodrama meetings corresponds or not to school complaints. It started from the hypothesis that the activities in educational psychology work associated with the psychodrama method enables children to express themselves and understand themselves as operant subject in the environment and can transform it according to their actions. It sought to answer the following questions: What are the school's complaints about the children? How children express themselves on different techniques of Pedagogical Psychodrama? The ways in which children express themselves in Pedagogical Psychodrama meetings corresponds or not to the school's complaints? The research universe was an OSCIP located in São Paulo and the subjects were 7, namely: 2 teachers of the regular school where children study and 5 children who compose the group. The methodology used was of qualitative nature of the intervention-research type and the data collection instrument were meetings with use of psychodrama method with a group of 5 children with school problems, beyond semi-structured interviews with two teachers. The speeches of children and teachers were analyzed guided by the Bardin content analysis (2012). The research was based on authors who discuss the following categories: Pedagogical Psychodrama: Maria Alicia Romaña and Alicia Fernández, Psychodrama: Moreno. As for the results it was found that at the beginning of the meetings children showed insecurity and lack of interest, but gradually became curious by the proposed work once it allowed moments of acceptance, awareness and self-reflection, allowing questions and apprenticeship shared in the group action, which influenced the decision-making, enabling the leadership. It was concluded that the educational psychodrama by giving voice to children enables them to express themselves so that they perceive them as acting subjects in the environment being able to transform it, they experience through the dramatization the conflict situations lived in daily life being able to reflect on them.